Exercício físico de baixa intensidade na DPOC: comparação dos programas solo e aquático - Araújo, Zênia Trindade de Souto (2009)
Physical Exercise (PE) is a necessary component in the management in COPD patients, where respiratory symptoms are associated with reduced functional capacity. Even with the increase in the number of studies that have been published and the therapeutics success using aquatic therapy approach, studies using PE in water in COPD patients are so few. Objective: the aim of this present study was to analyze the effects of low intensity water exercise in COPD patients, developed in two different places aquatic and ground. Methods: This is a randomized clinical trial study, 42 patients with moderate to very severe DPOC were recruited for the study, mean age of 63,2  10,9 years old. Randomized in 3 groups: Control Group (CG), Land Group (LG) and Water Group (WG). The PE protocol was performed in a period of 8 weeks, with frequency of 3 times per week. The CG participated in an educational program. All the patients were assessed twice through spirometry, respiratory muscular strength, the 6-min walk test, the quality of life (SF-36 and SGRQ), the LCADL, the MRC, the BODE index and the upper limbs (UP) incremental test. Results: There was a significant difference after the approaches in DP6 from the WG (p=0,02); in VEF1 in LG (p=0,00) and WG (p=0,01); in MIP in LG (p=0,01) and WG (p=0,02); in MEP in LG (p=0,02) and WG (p=0,01); the MRC decreases in WG (p=0,00). there was an increase of the weight supported by the UP in LG (p=0,00) and WG (p=0,01). The LG showed an increase of the quality of life represented by the SGRQ total score (p=0,00). The BODE index decreased in LG (p=0,00) and WG (p=0,01). In LCDAL, the LG showed a decrease. Conclusion: This data in this present study suggest that both approaches of low intensity exercise showed to be beneficial in moderate to very severe COPD patients. The WG showed additional benefits in physical function, pointing to a new therapeutic modality for COPD patients